Efektivitas Teknik ALBA Dalam Meningkatkan Kemampuan Membaca Permulaan Bagi Anak Lamban Belajar (Slow Learners ) Kelas III di SD Negeri 12 Kuamang - Sefria Lola Sari; Kasiyati Kasiyati (Jurnal Penelitian Pendidikan Khusus, 2019)
This research was based on the problems found in the field that slow learners in class III children who cannot read. Therefore, the researcher seeks to help children improve word reading skills through alba techniques. This study aims to improve the ability to read the words of a class III slow learner at SD Negeri 12 Kuamang.This type of research is single subject research (SSR). The design of this study is A-B-A.The results of this study indicate that the reading ability of the slow-learning tribe of children in Grade III at SD Negeri 12 Kuamang increased after intervention with the ALB technique. In the initial condition the child gets the highest score of 30%, the intervention condition of the child gets the highest score is 80%, while in the condition after no longer given intervention (A2) the child gets the highest score of 83%. Thus it is proven that the ALBA technique can improve reading skills in slow learners at SD Negeri 12 Kuamang. Based on the results of the study, the researcher advised the teacher to use the ALBA technique as a technique to improve reading skills for slow learning children.